2012
DOI: 10.1371/journal.pcbi.1002368
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Energy Landscapes of Riboswitches Help Interpret Conformational Rearrangements and Function

Abstract: Riboswitches are RNAs that modulate gene expression by ligand-induced conformational changes. However, the way in which sequence dictates alternative folding pathways of gene regulation remains unclear. In this study, we compute energy landscapes, which describe the accessible secondary structures for a range of sequence lengths, to analyze the transcriptional process as a given sequence elongates to full length. In line with experimental evidence, we find that most riboswitch landscapes can be characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 107 publications
2
52
0
Order By: Relevance
“…effective K d ) and kinetic factors (e.g. RNA folding and RNA polymerase rate) within its folding window (Quarta et al, 2012). High concentrations (10 mM) of Mg 2+ could also induce transcription read-through (data not shown), presumably by favoring the bound-like aptamer structure, a typical observation in diverse riboswitch families (Hennelly et al, 2013; Holmstrom et al, 2014; Santner et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…effective K d ) and kinetic factors (e.g. RNA folding and RNA polymerase rate) within its folding window (Quarta et al, 2012). High concentrations (10 mM) of Mg 2+ could also induce transcription read-through (data not shown), presumably by favoring the bound-like aptamer structure, a typical observation in diverse riboswitch families (Hennelly et al, 2013; Holmstrom et al, 2014; Santner et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Intermediate states expose details of the landscape that are particularly important for understanding those riboswitches that act co-transcriptionally . Because the competition between aptamer-and expression platform in this context is highly sensitive to the presence of kinetic traps, certain folding intermediates can play an outsized role in the regulatory decision, in a manner which cannot be handled satisfactorily by existing theoretical or computational approaches (however, recent work involving the prediction of different possible secondary structures during simulated elongation of nascent riboswitch RNAs shows promise [118, 119]). Studies of folding intermediates can also reveal the roles played by divalent cations (section 5.5 ) and the interplay between secondary and tertiary structure formation (section 5.4 ).…”
Section: Discussionmentioning
confidence: 99%
“…But the post-transcriptional full-length pbuE riboswitch was found to be fixed in the ligand-incompetent structure even when adenine is at saturation level, 32,35,38 which suggested that the regulatory activity should be in the transcription process. During transcription elongation, because the upstream RNA section folds first, this will influence the folding pathway of the downstream RNA section.…”
Section: Introductionmentioning
confidence: 99%